Adaptability of Naked Barley Landraces in Mountain Agro-ecosystem of Nepal - Ghimire, Krishna Hari; Joshi, Bal Krishna; Gurung, Rita; Palikhey, Epsha; Pudasaini, Niranjan; Parajuli, Aruna (Journal of Nepal Agricultural Research Council, 2019)
Naked barley (Hordeum vulgare var. nudum L.) is an important food crop in mountain regions of Nepal, however, its production area and genetic diversity is known to be shrinking fast. One of the reasons could be the poor productivity. To improve the productivity of crops, it is essential that new site-specific, high-yielding and widely adopted varietal options for farmers should be developed for sustainability. To identify the varietal responses to environment, multi-location testing is one of the main tools. Following this, we evaluated agronomic performance of eight naked barley landraces collected from five different locations of Nepal with altitude ranging from 1370 to 2500 meter elevations from the sea level during the winter season of 2014/15 in order to assess the landraces adaptability across different locations. Combined analysis of variances revealed that NGRC02306, NGRC04902 and NGRC04894 were the high yielding landraces. The landrace namely NGRC04894 was found the most stable genotype with better adaptability to all tested environments whereas NGRC02306 and NGRC04902 were high yielding landraces adapted to high yielding environment namely Khumaltar. However, the lower yielding landrace NGRC02327 was the earliest and could be preferred by farmers as its maturity allows it to fit better in the rice based cropping system. Our study showed that these landraces need to be verified further in farmers’ fields and the release of one or more of them would help to diversify the genetic base of naked barley varieties in the seed supply system.